Long-term Follow-up of Preterm Infants Having Been Colonized With Extended Spectrum Beta-lactamase–producing Enterobacterales Over the First 6 Years of Life. Issue 9 (13th July 2021) - Eberhart, Martin; Grisold, Andrea; Lavorato, Michela; Resch, Elisabeth; Trobisch, Andreas; Resch, Bernhard
Abstract : We performed a retrospective case-control cohort study following 146 preterm infants (≤32 weeks of gestation) who had been colonized with extended spectrum beta-lactamase producing Enterobacterales and compared them with 1:1 matched controls regarding rates of hospitalizations and outpatient visits because of infectious and gastrointestinal diseases and developmental impairment up to school age. Preterm infants with extended spectrum beta-lactamase producing Enterobacterales colonization did have neither higher rates of gastrointestinal or infectious diseases nor higher rates of developmental impairments up to the age of 6 years.